2006
DOI: 10.1074/jbc.m510290200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Mammalian 39-kDa Poly(ADP-ribose) Glycohydrolase

Abstract: , are located in a region similar to that required for activity in ARH1 but different from the location of the critical vicinal glutamates in the PARG catalytic site. All findings are consistent with the conclusion that ARH3 has PARG activity but is structurally unrelated to PARG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
298
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(321 citation statements)
references
References 44 publications
7
298
1
2
Order By: Relevance
“…In the case of PARG, there are about 50 000 molecules in mammalian cells [14,33], and following the 90 % silencing achieved with the present protocol, about 5000 PARG molecules would escape down-regulation. In addition ADP-ribose-(arginine) protein hydrolase 3 (AHR3) catalyzes an alternative enzymatic activity for the degradation of poly(ADP-ribose) and must therefore be taken into account for residual PAR degradation activity within PARG-silenced cells [34]. However, at this level, we see a dramatic accumulation of PAR molecules (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In the case of PARG, there are about 50 000 molecules in mammalian cells [14,33], and following the 90 % silencing achieved with the present protocol, about 5000 PARG molecules would escape down-regulation. In addition ADP-ribose-(arginine) protein hydrolase 3 (AHR3) catalyzes an alternative enzymatic activity for the degradation of poly(ADP-ribose) and must therefore be taken into account for residual PAR degradation activity within PARG-silenced cells [34]. However, at this level, we see a dramatic accumulation of PAR molecules (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…tankyrases, reviewed in 22) that take place outside the nucleus. Hydrolysis of PAR chains created by other PARPs is likely to involve PARG or ARH3 23 . It is possible that these PARG inhibitors prevent such processes but modification of this assay would have to be undertaken to detect non-nuclear PAR.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that ARH3 possesses poly(ADPr) glycohydrolase activity (10). The linkage hydrolyzed by ARH3 and ARH1 in poly(ADP-ribose) is also stereospecific at the C-1Љ position with the ␣-anomer present in the polymer (Fig.…”
mentioning
confidence: 92%
“…Three known members (ARH1-3) of the ARH family of proteins are similar in molecular size (ϳ39 kDa) and amino acid sequence (10). As noted above, ARH1 catalyzes the hydrolysis of ADP-ribose-arginine and also hydrolyzes ADP-ribose linkages to guanidine.…”
mentioning
confidence: 95%